Prevalence and Molecular Detection of Rotavirus in Children in Ramadi City-Iraq (Medico Legal Update, 2020)
Matter: This is the first study in Al-Anbar governorate with this design aim to the detection of rotavirusgroup A (ROVA).Method: A total of (150) stool samples obtained from children